10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Introduction Toscana virus (TOSV) and Leishmania species are sand fly-borne pathogens that pose a significant public health threat and an increasing risk of exposure in Europe. The objective of this study was to identify the phleboviruses circulating in an area endemic for sand fly-borne pathogens and to estimate infection prevalence in wild sand fly populations. We also aimed to analyse co-infections with L. infantum and the symbiotic bacterium Wolbachia. Methods The study was conducted in southern Spain. Sand flies were collected using CDC light traps, morphologically identified and DNA/RNA was extracted individually or in pools. A generic RT-nested PCR was used to detect phleboviruses, followed by sequencing and phylogenetic analysis. Leishmania infantum loads were quantified by qPCR, and Wolbachia was detected by PCR. Results We found that 2/443 individual sand flies (0.45%) and 8/64 pools (12.5%) were infected with phleboviruses, with an estimated prevalence of 1.9%. We confirm the circulation of TOSV-lineage B, together with Massilia-like virus and Alcube virus, in three sand fly species, and report novel strains of these phleboviruses. In addition, two Phlebotomus perniciosus individuals were co-infected with TOSV-lineage B and Wolbachia wPrn. We also detected L. infantum in 27.6% (60/217) of individuals, 66.7% (40/60) of which were co-infected with Wolbachia. Mean L. infantum loads [log-(parasite load +1)] in specimens co-infected with Wolbachia were not significantly different from those in uninfected specimens (p = 0.4). Conclusions This study provides further evidence for the continued circulation of TOSV and other phleboviruses in sand fly populations in southern Spain, with an estimated prevalence higher than that reported in the same region over a decade ago. Our study provides the first evidence of co-infection with TOSV-lineage B and Wolbachia in P. perniciosus, as well as a high proportion of specimens co-infected with Wolbachia and L. infantum. Understanding these co-infection dynamics is essential to elucidate the potential role of Wolbachia and the impact of Leishmania-phlebovirus co-infection on transmission.